Knowledge accumulation in Asian public administration research: A critical review - Ko, Kilkon (2013)
Given the growing controversy over the relevance of Anglo-Saxon style public administration to developing countries and a greater demand for more context-relevant theories of public administration in Asia, we should expect that Asian scholars achieve a certain level of knowledge growth in line with this controversy and demand. On the basis of the review of 8810 articles published in nine major international journals during 1990-2011, the author found that the number of articles on Asian public administration is very small, and there is no strong pattern of growth in this regard. In addition, there are very few studies adopting a comparative approach covering multiple Asian countries. - Reproduced. 10
Keywords: Public administration